ANALISIS USHUL FIKIH MENGENAI KALENDAR ISLAM DALAM KONTEKSTUALISASI NASH-NASH HISAB DAN RUKYAT - Saifurrohman, Ahmad; Azzafi, Ashif (IAIN Tulungagung, 2020)
In modern era, in line with the rapid development of astronomy, many new problems arise. For example, the issue in the Islamic calendar which has long been debated is the difference in determining the beginning of the month of Ramadan, Shawwal, and Zulhijjah or Arafat. From the above issue, what exactly the problem is the unification of the Islamic calendar and how the reckoning experts and astronomers in the effort to unify the Islamic calendar. To solve these problems requires the right way such as the infant method or textual analysis, the causation method, and the taufiki method. Keywords: Unification of the Islamic Calendar, Islamic Calendar, Bayani, Causation, Taufiki, Interpretation.